Analysis of Media Framing of Online Media Coverage of Protests Against the 2025 TNI Law (A Comparative Study of Tempo.co, Kompas.com, and Metronews.com) - Mohamad Rizky Djaba; Ainun Nimatu Rohmah (International Journal of Sociology of Religion, 2025)
This study aims to critically examine how framing practices in online media reporting shape public perceptions of demonstrations against the ratification of the Indonesian National Armed Forces Act (TNI Act). Using the framing theory developed by Robert N. Entman, this study analyzes and compares three news articles published by Kompas.com, Metrotvnews.com, and Tempo.co. The main focus of the study is on identifying framing patterns that encompass four main dimensions: problem definition, causal interpretation, moral evaluation, and recommendations for addressing the issue. This study uses a qualitative approach with critical discourse analysis within the framework of Entman's framing analysis. The objects of study are three news reports covering the demonstrations against the TNI Law and the revision of the Polri Law that took place on March 27, 2025, in the area of the DPR Building, Central Jakarta. Each text is analyzed systematically to examine the construction of the narrative and the differences in perspective raised by each media outlet. The results of the study show that Kompas.com and Tempo.co tend to frame the demonstrations as a form of civil resistance against state policies that are considered to threaten the principles of democracy and civil supremacy. In contrast, Metrotvnews.com emphasizes the dimension of public order, highlighting the dispersal of the crowd by the authorities as a measure to restore social stability. These findings reinforce the argument that media plays a strategic role in shaping public discourse and the direction of collective perceptions toward political issues and state policies.